Different pretreatment technologies of lignocellulosic biomass for bioethanol production: An overview. (15th May 2020) - Rezania, Shahabaldin; Oryani, Bahareh; Cho, Jinwoo; Talaiekhozani, Amirreza; Sabbagh, Farzaneh; Hashemi, Beshare; Rupani, Parveen Fatemeh; Mohammadi, Ali Akbar
Abstract: Regarding the supply of fossil fuels, greenhouse gasses emission, global warming, and increasing fuel price; there is a need to find alternative energy resources, which are renewable, environmentally sustainable, and economically viable. Agro-industrial biomass such as sugarcane bagasse, rice and wheat straw, corn stover, and switchgrass, named as lignocellulosic biomass (LCB) which is inexpensive, abundant, renewable, and provides a unique natural resource for large-scale and cost-effective bio-energy production. During the production of biofuels, pretreatment is a necessary step due to the recalcitrant structure of LCB. Various pretreatment methods were employed with a different mechanism of action, feasibility, and practicability to produce high yield biofuels. Since many years ago, the development of an effective pretreatment method has been challenging due to the existence of barriers and obstacles. Besides, each pretreatment method has its advantage and disadvantage, which should be investigated to obtain a higher yield of bioethanol. In this paper, the recent findings regarding the application of various pretreatment techniques such as chemical, physical and biological methods for bioethanol production from LCBs have been reviewed. The limitations of the mentioned methods based on the existing barriers were explained, and the future recommendations were discussed. Highlights: Recent progress in bioethanol production from LCB using different pretreatments methods is reviewed. The efficiency of various pretreatments methods has a direct effect on production yield. The selection of a suitable method should be based on the biomass structure. Future studies should focus on the process optimization of combined methods.